OPTIMASI PEMANFAATAN TOGA DALAM PENCEGAHAN PENYAKIT TIDAK MENULAR BERBASIS EDUKASI - Rissa, Mexsi Mutia; Arianto, Machfudz Eko; Marsellinda, Elsa (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2026)
Non-communicable diseases (NCDs), particularly hypertension, remain a major public health concern associated with unhealthy lifestyles and limited utilization of local resources such as family medicinal plants (TOGA). This community service activity aimed to improve community knowledge and skills in utilizing TOGA as a preventive strategy against hypertension. The methods included health screening through blood pressure measurement, health education on hypertension and TOGA, and hands-on training in TOGA cultivation. The activity was conducted among women aged 35–55 years in RT 26 Wonocatur. The results showed an improvement in participants’ knowledge and understanding, as reflected by their ability to explain the material and perform TOGA planting independently. The screening results also indicated the presence of participants with elevated blood pressure, highlighting the urgency of the intervention. The combination of education and practical training proved effective in enhancing community participation and awareness of NCD prevention. This approach has the potential to be developed as a sustainable community-based promotive and preventive strategy.